Research of the concept of polysensory branding and the possibilities of its adaptation to the web communication environment - I. Yu. Aleksandrova (E-Management, 2023)
The concept of polysensory branding and the problem of its adaptation to the web environment are investigated. The content specificity, genesis and psychological basis of the concept of polysensory branding are carried out. The article analyzed the «Smash your brand» technique, developed by Martin Lindstrom, in order to test the communicative effectiveness of the twelve components of the brand identity system, focused on different channels of perception. In order to scientifically substantiate the practical significance of the tools of polysensory branding and sensory marketing in an offline environment, the results of an empirical study conducted under the guidance of the author are considered. The empirical research is aimed at the identifying the impact features of the of the brand’s olfactory communication system on consumers. The study reveals the dependence of brand perception and consumer activity on the specifics of marginal suggestive aromatization of the store’s sales area. The problem of the limitations of sensory channels of brand communications in the web environment is studied, in particular, the impossibility of mechanical transfer of polysensory branding tools to the web environment due to technical limitations, as well as the peculiarities of the psychology of perception and behavior of online users. As a result of the conducted study, possible channels and tools for the implementation of brand polysensory web communications are identified and systematized, the author’s psychological model of the brand’s multi-channel communicative field is developed, which includes a mechanism for adapting offline channels of polysensory branding to the web communication environment.